2022
DOI: 10.1371/journal.pone.0264027
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel stripe rust resistance gene from the European winter wheat cultivar ‘Acienda’: A step towards rust proofing wheat cultivation

Abstract: All stage resistance to stripe rust races prevalent in India was investigated in the European winter wheat cultivar ‘Acienda’. In order to dissect the genetic basis of the resistance, a backcross population was developed between ‘Acienda’ and the stripe rust susceptible Indian spring wheat cultivar ‘HD 2967’. Inheritance studies revealed segregation for a dominant resistant gene. High density SNP genotyping was used to map stripe rust resistance and marker regression analysis located stripe rust resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Stripe rust can destroy the crop if the infection occurs very early [ 8 ]. The average wheat yield loss caused by stripe rust ranges from 25% to 80% worldwide [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stripe rust can destroy the crop if the infection occurs very early [ 8 ]. The average wheat yield loss caused by stripe rust ranges from 25% to 80% worldwide [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This QTL should be different from QYr.gaas-1AL based on a physical distance of about 220 Mb between them. Grover et al (2022) identified an ASR locus Yraci in the European winter wheat cultivar “Acienda” on the distal end of wheat chromosome 1A. Besides, two SNPs AX-95162217 and AX-94540853 linked with Yraci were mapped in the bin at 54.04 cM on chromosome 1A, whereas QYr.gaas-1AL covered a physical interval of 505.3–506.8 Mb on chromosome 1A was far away from Yraci .…”
Section: Discussionmentioning
confidence: 97%
“…The existing 35K Axiom™ wheat breeder’s genotyping array designed in 2011 has been widely used by academics and breeding companies with 288 citations in research areas recently spanning pathogen resistance (Nannuru et al . 2022, Grover et al . 2022), yield (Sheoran et al .…”
Section: Discussionmentioning
confidence: 99%